2018
DOI: 10.1139/cjfr-2017-0307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of substrate availability and competing vegetation on natural regeneration of white spruce on logged boreal mixedwood sites

Abstract: Given a seed source, the quality of available substrates is a key factor in determining the success of white spruce (Picea glauca (Moench) Voss) natural regeneration. We examined the influence of substrate and competing vegetation on survival and growth of natural regeneration of white spruce up to 4 years following harvesting in deciduous-dominated upland boreal mixedwood sites. Feather moss, thick soil surface organic layers, litter, and solid wood were poor substrates for establishment. Early successional m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In any case, the biomass of the planted seedlings would add up to the one of the naturally regenerated seedlings as it is unlikely that the two types of seedlings engage in a strong competition, at least in this time frame. The planted seedlings may even have a protective effect (mainly against wind) and thus increase the survival and the growth of the natural seedlings in the first years (Kokkonen et al, 2018). Therefore, afforestation seems to be necessary to accumulate enough biomass in the mid-term to compensate for soil C emissions resulting from soil scarification.…”
Section: Seedling Size Age and Establishment Dynamicsmentioning
confidence: 99%
See 3 more Smart Citations
“…In any case, the biomass of the planted seedlings would add up to the one of the naturally regenerated seedlings as it is unlikely that the two types of seedlings engage in a strong competition, at least in this time frame. The planted seedlings may even have a protective effect (mainly against wind) and thus increase the survival and the growth of the natural seedlings in the first years (Kokkonen et al, 2018). Therefore, afforestation seems to be necessary to accumulate enough biomass in the mid-term to compensate for soil C emissions resulting from soil scarification.…”
Section: Seedling Size Age and Establishment Dynamicsmentioning
confidence: 99%
“…Mosses, however, can have contrasting effects on seedling establishment and growth depending on species and locations. For instance, early successional mosses developing on mineral soil patches have been shown to facilitate white spruce seedling establishment at several Canadian boreal sites, whereas feather mosses had the opposite effect (Kokkonen et al, 2018). More specific research must be conducted to assess the rate of colonization by both lichen and moss species, and their specific effect on the dynamics of seedling establishment in the LWs of the study area.…”
Section: Seedling Size Age and Establishment Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may indicate different mechanisms for seedling survival and growth, as well as different modes of action for mosses and shrubs, such as facilitation or competition. Earlier findings have shown that the presence of mosses can be a great barrier for seedling germination and survival in the boreal forest (Valkonen and Maguire, 2005;Hypponen et al, 2013;Kokkonen et al, 2018) and relate that to changes in moisture (Lindo and Gonzalez, 2010;Soudzilovskaia et al, 2013) and competition for space as mosses can also suffocate tree seedlings (Stuiver et al, 2014). Shrubs have also been shown to suppress seedling growth (Wardle et al, 2008), e.g., E. hermaphroditum is known to produce poor quality litter with allelopathic compounds hampering seedling establishment (Nilsson and Zackrisson, 1992).…”
Section: Seedling Performance and Understory Functional Groupsmentioning
confidence: 99%